Simulation applied to stretcher management: improvements in patient flow in a public hospital in Feira de Santana - Cerqueira, Eduardo Abreu Batista; Araújo, Andressa Clara Barbosa de; Pimentel, Cristiane Agra (Brazilian Journal of Production Engineering, 2025)
The study explores the use of Industry 4.0 technologies in healthcare, focusing on simulation to optimize stretcher-bearer workflows, a relatively underexplored area. Efficient workflows are crucial for the safe transport of patients, directly impacting care quality and hospital resource management. The objective was to use simulation to improve stretcher-bearer workflows in a public hospital in Feira de Santana specializing in maternal and childcare, reducing wait times and optimizing movements. This descriptive research modeled current and future scenarios using FlexSim 24.0.4 software, with data collected from June to October 2024 during the busiest shifts. In the current scenario, a single stretcher-bearer covered 4.10 km per shift, whereas, in the future scenario with two stretcher-bearers, distances decreased to 2.67 km and 2.58 km, respectively. Travel times were reduced, and time available for patient care increased, enhancing operational efficiency. Simulation proved to be an effective tool for logistics optimization, improving care quality and working conditions. These findings highlight the methodology's potential for application in other hospital areas.
Keywords: Hospital Simulation; Hospital Management; Health 4.0